Non-Verbal Elements as Primary Attentional Anchors Across Generational Cohorts: Eye-Tracking Evidence from Multimodal Communication Context - Rizki Edmi Edison; Deni Adha Akbari; Pratiwi Cristin Harnita; Widya Yanti Sihotang (Jurnal Arbitrer, 2026)
Contemporary multimodal communication environments integrate verbal with non-verbal elements within unified communicative artefacts spanning health, commercial, digital, and persuasive discourse. Despite theoretical consensus in multimodality and semiotics that non-verbal and verbal modes carry distinct processing affordances, objective neurophysiological evidence for the attentional priority of non-verbal elements, and its consistency across generational cohorts, remains limited in the literature. This study aims to investigate whether non-verbal visual elements consistently capture first visual fixation before verbal elements across multiple multimodal communication contexts, and to examine whether this attentional pattern is consistent across two generational cohorts, Generation Z and Millennials. A cross-contextual multi-study synthesis design was employed, integrating eye-tracking data from four previously published empirical studies conducted at Universitas Prima Indonesia and Universitas Muhammadiyah Prof. Dr. HAMKA. Across all four studies, non-verbal elements captured first fixation in almost all of participants, although no statistically significant inter-cohort difference was observed within one of studies. These findings provide neurophysiological evidence that non-verbal visual elements constitute universal primary attentional anchors in multimodal discourse, functionally independent of communicative context and generational cohort. The results carry direct implications for language-sensitive communication design, plurilingual health messaging, multimodal pedagogy, and the theoretical understanding of verbal–non-verbal semiotic hierarchies in multilingual and multicultural communication environments.